Speech Function in the 2024 Indonesian Presidential First Debate Candidates - Ayu Ambarwaty, Ajeng; Hidayati; Wardana, Kiki (PT PUSTAKA CENDEKIA GROUP, 2025)
A leader must use good and correct language. Judgment and attitude of a speaker are important. The use of good and correct language is one good way to maintain the judgment and attitude of a speaker. It is needed wherever and whenever. The researcher used Halliday’s theory of systemic functional grammar, focusing on the interpersonal function. The research was carried out using the qualitative method, and is presented descriptively. This research used the opening speeches at the 2024 Indonesian presidential first debate candidates as data. This research examines the speech functions in the speeches delivered by the three 2024 presidential candidates. The data is in the form of a speech text taken from a website (Akbar, 2023a, 2023c, 2023b) which was then selected for the clauses contained in it. The clauses contained in this speech are 108 which means this research has 108 data. As a result, it was discovered that out of the 108 clauses in the 2024 Indonesian presidential first debate candidates, 80,5% fall under the Statement type, 10,2% fall under the Question type, and the remaining 9,2% comprises the modulated interrogative moods. There is no Offer type in this research.